Effect of yoga on female hormones in peri-menopausal women - Khadka, Rita; Paudel, Bishnu Hari; Lamsal, Madhab; Shrestha, Nikesh; Regmi, Mohan Chandra; Chhetri, Sailaja; Karki, Prahlad (Journal of Physiological Society of Nepal, 2022)
Background : One of risk factors for increased rate of cardiovascular diseases and development of menopausal symptoms in perimenopausal/postmenopausal women is reduced estrogen production. Yoga practice improved menopausal symptoms in postmenopausal women. Whether yoga practice had effect on estrogen in perinomopausal/postmenopausal women was not known. Thus, this study was conducted to assess the effect of yoga on female hormones; estrogen, progesterone, luteinizing hormone (LH), and follicular stimulating hormone (FSH) in perimenopausal women.Methods : The study included 60 perimenopausal women, grouped into yoga (n=30, age 44±2.64 years) and control (n=30, age 46±5.09 years) groups. The yoga group practiced meditation, pranayama and few simple asanas for 40 min/day, 6 days/week for 4 weeks. The control group did not practice any kinds of exercise. Levels of female hormones were assessed in all subjects at the beginning of the study and after four weeks of the study, and compared statistically. Institutional Ethical Committee approved the study.Results : Age, body mass index (BMI), blood pressure (BP), Heart rate (HR), and respiratory rate were comparable between the groups at the beginning of the study. Hormones LH and FSH showed no significant changes within and between group comparisons. Serum estrogen [11.95 (5.05-41.32) vs 24.47 (12.54-64.90) pg/ml, p=0.036] and progesterone [0.24 (0.10-1.02) vs 2.0 (0.25-9.73) ng/ml, p=0.012] increased in yoga group after yoga practice in within group comparisons, whereas, the control group showed no changes.Conclusion : Estrogen and progesterone levels increased in perimenopausal women after four weeks of yoga practice, whereas, LH and FSH showed no changes. It reveals that yoga practice can have cardio protective effects in perimenopausal women.